Methodological reflections on research with street youth. (September 2018) - Karabanow, Jeff; Kidd, Sean; Frederick, Tyler; McLuckie, Alan; Quick, Jacqueline
Summary: This paper examines both the epistemological and practical limitations and challenges of data collection by reflecting on the experiences of a team of both junior and senior researchers engaged in such a longitudinal study. Findings: This paper argues that longitudinal research with street youth challenges the boundaries and limits of the formal constructs of research and ethics that typically guide qualitative research by grappling with field issues such as navigating reciprocity, risk and authenticity within relationships with a vulnerable group. Application: This paper calls for an explicit acknowledgement of the challenges researching populations such as street youth over time in our research ethics guidelines and encourages researchers to engage in dialogue leading to more reflective, transparent and accountable framing of how we collect data in the field with vulnerable youth populations.